2005
DOI: 10.1080/13554790500263503
|View full text |Cite
|
Sign up to set email alerts
|

A stimulus-centered reading disorder for words and numbers: Is it neglect dyslexia?

Abstract: A single case, RCG, showing a unilateral reading disorder without unilateral spatial neglect was studied. The disorder was characterized by substitutions of the initial (left) letters of words, nonwords and Arabic numbers, independently of egocentered spatial coordinates. MRI showed a bilateral lesion with the involvement of the splenium. Although, within the framework of the visual word recognition model proposed by Caramazza and Hillis (1990), RCG disorder could be defined as a stimulus-centered neglect dysl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…We speculate that in those patients the number of substitutions should reduce as a function of letter spacing. In agreement with this conjecture, a patient RCG, described by Arduino et al (2005), shows a predominance of substitution errors in reading (93% of 106 errors on 240 words) and halves the number of errors when letter spacing is increased (44 on 240, result unpublished in the cited study).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We speculate that in those patients the number of substitutions should reduce as a function of letter spacing. In agreement with this conjecture, a patient RCG, described by Arduino et al (2005), shows a predominance of substitution errors in reading (93% of 106 errors on 240 words) and halves the number of errors when letter spacing is increased (44 on 240, result unpublished in the cited study).…”
Section: Discussionsupporting
confidence: 79%
“…As both types of disrupted mechanisms can occur in the same patient, each deficit can be predicted on the basis of the observed errors and vice versa. In particular, when patients with neglect dyslexia and without USN are found, they should show a predominance of substitution errors and, in fact, this is exactly what has been found (see e.g., Arduino, Daini, & Silveri, 2005;Haywood & Coltheart, 2001;Katz & Sevush, 1989;Patterson & Wilson, 1990). We speculate that in those patients the number of substitutions should reduce as a function of letter spacing.…”
Section: Discussionmentioning
confidence: 79%
“…In our patient the side of visual field impairment and of neglect dyslexia dissociated, which is comparable to left-hemisphere damaged patients. Finally, the present case is reminiscent of the patient described by Arduino et al (2005), who following bilateral temporo-occipital damage presented a stimulus-centred left neglect dyslexia. This patient showed right upper quadrantanopia with no signs of neglect other than in reading and cerebral hypoperfusion that was more important in the left than the right hemisphere, suggesting that his left-hemispheric lesion may have caused his reading impairment.…”
Section: Discussionmentioning
confidence: 97%
“…Among the classic paper-and-pencil tests used to assess neglect line bisection appears to be the only significant predictor of neglect dyslexia (Ptak et al, 2012;Reinhart et al, 2013). Nevertheless, several case studies of 'pure' neglect dyslexia (i.e., dyslexia without other neglect symptoms; Arduino et al, 2005;Haywood and Coltheart, 2001;Riddoch et al, 1990) or of dyslexia that is dissociated from other signs of neglect (e.g., left dyslexia with right neglect in cancellation tasks; Costello and Warrington, 1987;Cubelli et al, 1991;Humphreys and Riddoch, 1995) have been reported. However, all patients classified as 'pure' neglect dyslexics had at least partial visual field loss that may have influenced the reading disorder, in particular if combined with subclinical symptoms of neglect.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of a cueing effect has also been found in a patient, R.C.G., who has problems reading the beginnings of words(Arduino, Daini, & Silveri, 2005). However, R.C.G.…”
mentioning
confidence: 91%